2019
DOI: 10.1136/bmjopen-2019-031271
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and hospitalisation costs of spinal muscular atrophy in Spain: a retrospective multicentre database analysis

Abstract: ObjectivesTo analyse the characteristics of patients diagnosed with spinal muscular atrophy in Spain, and to revise data on disease management and use of resources in both public and private healthcare centres.DesignA retrospective multicentre database analysis.Setting870 admission records registered between 1997 and 2015 with a diagnosis of spinal muscular atrophy were extracted from a Spanish claims database that includes hospital inpatient and outpatient admissions from 313 public and 192 private hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…Of these, 289 were duplicates, 665 were excluded following title and abstract screening, and 29 were selected for fulltext review. Finally, 14 articles [13][14][15][16][17][18][19][20][21][22][23][24][25][26] were considered for data extraction and synthesis. The primary reason for article exclusion was lack of relevant cost data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 289 were duplicates, 665 were excluded following title and abstract screening, and 29 were selected for fulltext review. Finally, 14 articles [13][14][15][16][17][18][19][20][21][22][23][24][25][26] were considered for data extraction and synthesis. The primary reason for article exclusion was lack of relevant cost data.…”
Section: Resultsmentioning
confidence: 99%
“…Nine (64%) studies reported estimates of costs of SMA type I [ 15 18 , 20 23 , 25 ], four (29%) of costs of SMA type II [ 13 , 20 , 22 , 25 ], four (29%) of costs of SMA type III [ 15 , 20 , 22 , 25 ], one (7%) of costs of SMA type IV [ 21 ], and one (7%) study of costs of progressive SMA, other SMA, and unspecified SMA [ 15 ]. Eleven (79%) studies did not explicitly disclose SMA type, or reported pooled results for more than one type of SMA (in some cases in addition to estimates stratified by SMA type, as reported above) [ 13 15 , 18 21 , 23 26 ]. Two studies (14%) estimated costs of “infantile SMA”, “childhood-onset SMA”, and/or “late-onset SMA” [ 21 , 23 ], for the purpose of this review approximated as SMA type I, SMA type II/III, and SMA type IV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond core symptoms (e.g. respiratory, motor function), clinical issues that can be more prominent in adults include excessive fatigue [10], kidney stones, osteoporosis, acidosis [11], hypertension [12], weight management, sexual health and hormonal issues. Often, adults also receive inadequate reproductive health advice, for example, being told that having a child is not possible/too dangerous despite many adults having uneventful pregnancies [13].…”
Section: Aspiration #1 Provide Age-appropriate and Comprehensive Care That Delivers The Most Meaningful Health Outcomes And Qol For Adultmentioning
confidence: 99%